The credibility of the Catholic Church as public actor - O'Loughlin, Thomas (Wiley, 2013)
This article assumes that there is a profound crisis of credibility in the Catholic Church today. This is distinct from the issue of the credibility of Christian faith or the credibility of theism, for many who believe, indeed many Catholics, are affected by this sense that the Church, as a public actor, lacks credibility. Moreover, while it would be a mistake to seek the roots of this lack of credibility within general appeals to “modern unbelief,” so it would also be a mistake to imagine that it is purely a matter of “image” or as a direct result of the revelations about clerical child-abuse and its cover-up. It argues that modern society has evolved, through painful experience, a healthy scepticism about large organisations and with this has developed a set of social values (e.g. mutual responsibility and transparency) that are at odds with many of the values (e.g. hierarchy) that the Church has inherited from its past. Far from seeing these developments as part of a pathology of modernity, they can be seen as the work of the Spirit and a challenge to the Church to embrace new ways of being a witness to the truth and new ways of embodying the Christ in its living.